EFEK GELOMBANG TSUNAMI ACEH 2004 PADA GANGGUAN IONOSFER BERGERAK SKALA MENENGAH DARI PENGAMATAN JARINGAN GPS SUMATRA - Asnawi Husin; Buldan Muslim (Universitas Riau, 2019)
Medium Scale Travelling Ionospheric Disturbance (MSTID), thought to be manifestation of atmospheric gravity wave (AGW) in the ionospheric altitude that propagates horizontally and effects on in the electron density structure of ionosphere. These atmospheric gravity waves sourced from lower atmospheric activities such as typhoons, volcanic eruptions and tsunamis. Wave energy by its coupling induction process can travel to the ionosphere region. It has been understood that the TID's wave structure have an impact on the propagation of radio waves in the ionosphere so that it will affect the performance of navigation satellite-based positioning measurements. Based on Aceh tsunami in December 2004, this study aimed to investigation of the induction of atmospheric gravity waves in the ionosphere using total electron content (TEC) data from the Sumatra GPS network (Sumatra GPS Array, SUGAR). The detection technique of TEC changes due to AGW induction with a filter to separate medium scale disturbance at the ionospheric pierce point at an altitude of 350 km (IPP, Ionospheric Pierce Point). The results show the horizontal wavelength of a medium-scale TID around 180 ± 12 Km with a velocities of around 376 ± 9 ms-1. Based on two-dimensional map, the TID moves to the southeast.